Rebuilding Zion: the holy places of Jerusalem in the twelfth century - Hamilton, Bernard (Studies in church history, 1977)
It is unusual for a period of Christian renewal to begin with a massacre, yet that is what happened when the crusaders entered Jerusalem on 15 July 1099. Raymond of Aguilers, chaplain of the count of Toulouse, boasted that they rode through moslem corpses heaped up in the Haram al-Sharif with blood ‘even to the horse bridles’ This should not obscure the fact that the crusading movement was motivated partly by a growing devotion to the humanity of Christ in the western church in the late eleventh century, or, as the author of the Gesta Francorum expressed it, a desire to ‘follow in the footsteps of Christ, by whom they had been redeemed from the power of hell’. It was this sentiment which led the crusaders to seek to restore the shrine churches of Jerusalem and in the eighty-eight years of their rule they filled the city with fine churches and monasteries closely resembling those which were being built in the west at the same time. It should be emphasised that the crusaders were seldom concerned to rebuild existing churches in Frankish style: their primary interest was to restore churches which had been ruined by war and persecution in the centuries of moslem rule. The pilgrim Saewulf, who visited the east four years after the Latin conquest, reported that ‘nothing has been left habitable by the Saracens, but everything has been devastated . . . in all. . . the holy places outside the walls. . . of Jerusalem’.